Design Criteria and Limitation for The Urban Park Design at City Level, Study Case Halep - Akkam, Mehmet Sair; Kucukali, Ufuk Fatih (Architecture Image Studies, 2023)
This urbanization throughout the early decades of the twentieth century was overwhelming even at the expense of the green areas of cities and rural areas. The provision of housing, employment and services to the growing population was a priority on the theme of “entertainment”. Thus, for the last three decades, the city's public parks and green areas have become increasingly popular in response to urban overcrowding and high urban densities, which resulted in environmental problems and visual pollution. The results of the urban tyranny against the green spaces in cities began to emerge; the city planners and decision-makers discovered that residents need gardens and parks no less than their needs for housing, work or services. The city, without a network of interconnected and gradual parks and public green areas, suffers from great environmental problems that put in danger its sustainability and the health of its citizens. In this dissertation, the character and the significance of public parks and green areas in the city shall be scrutinized. This will encompass the definition of history and roles of public parks at the city level; besides, what motivates the visitors to come and what they would be their needs in parks. Later, in the chapter 2, the factors that influence the design of public parks will examined; such as nature, social and physical factors and neighborhood data, and the choice of the park’s design systems will be conferred. Moreover, in the chapter 3, the design components of public park shall be enumerated; the physical, the aesthetic components and principles of parks’ design. Then, the design standards of public parks shall be appraised with their quantitative and qualitative aspects, this would include: the functions and services provided inside parks, the circulation system and paths as well as the plazas, the vegetation and water bodies and finally design criteria of the urban furniture inside the park. In the chapter 4, case studies from previous experiences shall be explored. The case studies examples concern two parks at the city center of Istanbul and Aleppo, they are Maçka Park in Istanbul/Turkey and The Public Park in Aleppo/Syria. Finally, the conclusion shall contain development remakes and results of the research and shall determine the future orientations of the research.